Gossip : the untrivial pursuit - Epstein, Joseph, 1937- (Boston : Houghton Mifflin Harcourt, 2011)
A juicy, incisive exploration of gossip in all its forms--from celebrity rumors to literary'romans a clef,' from personal sniping to political slander.
Includes bibliographical references (p. [221]-223) and index.
Keywords: Gossip